A new approach to shear design of slender reinforced concrete members without transverse reinforcement. (15th January 2016) - Tung, Nguyen Duc; Tue, Nguyen Viet
Highlights: The formation of the critical shear crack is explained. A shear band for the formation of shear crack is introduced. A calculation procedure to determine the shear capacity is presented. Verification with experimental data from the literature is performed. Effect of the structural system and load arrangement on the shear capacity is experimentally confirmed. Abstract: This paper presents the theoretical development of a new approach to determining the shear capacity of slender reinforced concrete members without transverse reinforcement. Taking into account the very small component of the normal stress of concrete in the tension zone, which is normally neglected when determining the bending capacity, it is assumed that the damage is potentially localized in a narrow band that tends to connect the tips of existing flexural cracks. The width of this band increases with the shear force and decreases with the increase of the bending moment. The shear failure is characterized by the formation of the critical shear crack in the shear band when its width reaches a critical value. With the new approach, the bending moment has a positive influence on the shear resistance of a cross-section, which contradicts most existing shear models. The validation of the new approach against experimental data shows that the proposed method accurately predicts the shear capacity of all investigated types of shear span. The influences of the structural system and load arrangement on the shear response observed from experimental investigations can be well captured.